The current neuroscientific understanding of Alzheimer's Disease - Rachel A Brandes (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2020)
Alzheimer’s disease is a degenerative neurological illness characterized by the deterioration of brain regions implicated in memory and cognitive function. While researchers have yet to find a cure or effective treatment, they have gained a better understanding of its pathology and development. Through years of neuroscience research, scientists have discovered much of what happens in the brain during Alzheimer’s disease onset and how this causes its symptoms; many hypotheses regarding this aspect of the illness involve temporal lobe atrophy, neurofibrillary tangles, and amyloid plaques. Although Alzheimer’s disease affects millions of people every day, it seems that most are unaware of how it affects the human body physiologically, emotionally, and psychosocially. Without knowing the main characteristics, physiological causes, and diagnostic criteria of this illness, it will remain difficult to recognize its presence within oneself, friends, and family members, which could prevent patients from receiving adequate care and supervision. Therefore, knowledge of the relationship between neuroscience and Alzheimer’s disease is essential; the following research and analysis explores scholarly works detailing this connection.